An integrated macro-model for the Caribbean subregion - Vinhas de Souza, Lucio (1997)
Calculates a simple integrated macro-model for the Caribbean subregion. Uses a homogenous data set that runs from 1980 to 1991 for a sample of 12 countries in the subregion and a fairly simple model with non-controversial specifications for the structural relationship, generates a representative and consistent group of estimates for a given set of parameters in pooled and individual country estimates.